Electrophysiological Evidence of Event-Related Potential Changes Induced by 12 h Abstinence in Young Smokers Based on the Flanker Study - Cui, Yongting; Dong, Fang; Li, Xiaojian; Xie, Dongdong; Cheng, Yongxin; Tian, Shiyu; Xue, Ting; Li, Yangding; Zhang, Ming; Ren, Yan; Yuan, Kai; Yu, Dahua (Frontiers in Psychiatry, 2020)
The cognitive control processes may be disrupted by abstinence in smokers, which may be helpful in the development and maintenance of addictive behavior. The purpose of this study was to measure the performance of cognitive task after 12 hours of smoking abstinence by using event-related potentials (ERP), including the error-related negativity (ERN) and the error positivity (Pe). In Eriksen flanker task, EEG signals of 24 smokers were recorded in two conditions: satiety and 12h abstinence. In the behavioral data, both conditions exhibited more errors and more time on the incongruent trials than congruence. Meantime, the Minnesota Nicotine Withdrawal Scale (MNWS) score was increased during abstinence. Smokers showed reduced ERN and Pe after 12h of abstinence, compared with satiety condition. The results indicate that the diminished error processing in young smokers after 12h of abstinence. It may be related to increased withdrawal symptoms. In conclusion, the disrupted neurophysiological indexes in the general behavior monitoring system may be caused by abstinence. The results of this study may provide us with new ideas about the effects of short-term abstinence on brain cognitive neuroscience and be helpful for the solution of relapse.